Comparative assessment of degradation in aqueous medium of polypropylene films doped with transition metal free (experimental) and transition metal containing (commercial) pro-oxidant/pro-degradant additives after exposure to controlled UV radiation. (October 2015) - Montagna, Larissa Stieven; Catto, André Luis; Camargo Forte, Maria Madalena de; Chiellini, Emo; Corti, Andrea; Morelli, Andrea; Campomanes Santana, Ruth Marlene
Abstract: The comparative behaviour to degradation of polypropylene (PP) films with 1 and 3 wt.% of experimental (transition metal free) and commercial (transition metal containing) pro-oxidant/pro-degradant additive were investigated under accelerated environmental conditions. Specimens of 20 μm films, obtained by extrusion of the samples of PP containing the pro-oxidant/pro-degradant additives, were initially exposed to irradiation in a UV chamber for 270 h, and then submitted to a degradation test in aqueous medium for 100 days. The CO2 production in response of a microbial attack was monitored by back titration during all the experimented trials. The PP crystallinity was evaluated by differential scanning calorimetry (DSC) and the oxidation level was determined by the determination of carbonyl index by Fourier Transform Infrared analysis (FT-IR). The surface morphology of the PP samples was investigated by scanning electron microscopy. A degradation evidence of the additivated PP samples was attained in comparison with the behaviour of neat PP samples. The surface of the additivated PP films showed grooves and holes as a clear indication of the physical-chemical degradation. The PP samples with the experimental metal-free pro-oxidant/pro-degradant experienced a higher level of degradation with respect to the PP sample loaded with the commercial transition metal containing pro-oxidant/pro-degradant. Thus, the benzoin/potassium salt free of transition metal suggested in this work has showed be highly efficient degradant additive for PP degradation.